2022
DOI: 10.1177/14750902221098304
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the effects of Vee-shaped steps on the hydrodynamic performance of planing hulls

Abstract: Speed and stability are two essential criteria for assessment of planing hull performance. Accordingly, the effects of step shape on these vessels’ hydrodynamic performance and stability are experimentally investigated. Five different models are studied which are based on a high-speed recreational craft and are primarily the same in form and dimensions. One of these models does not have a step, two of them have transverse steps, and two other models have Vee-shaped steps. These five models all have a length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Considering the absence of publicly available ship model test results, a V-shaped high-speed boat from the M 1 ship type proposed by Parviz Ghadimi [26] is selected to carry out a comparative study to assess the accuracy of the numerical methods. Table 6 lists the principal dimensions of hull M 1 while Fig.…”
Section: Validation Of the Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the absence of publicly available ship model test results, a V-shaped high-speed boat from the M 1 ship type proposed by Parviz Ghadimi [26] is selected to carry out a comparative study to assess the accuracy of the numerical methods. Table 6 lists the principal dimensions of hull M 1 while Fig.…”
Section: Validation Of the Numerical Methodsmentioning
confidence: 99%
“…The ship type studied in this paper was inspired by a catamaran with a step [16]. Using a step on the hull could separate the water, create a dry section from step to transom, and reduce the resistance at high speed [25][26]. The stepped hull is viewed as two regular hulls following each other closely, so that the catamaran turns into a quadramaran.…”
Section: Computational Modelmentioning
confidence: 99%
“…In the case of stepped hulls, Sajedi et al [29] probed how a single-stepped hull with a step at 30% of vessel length to its stern performs in calm water and Froude numbers from 0.43 to 3.87. Te efects of vee-shaped steps on the hull's performance and how they difer from transverse steps have been experimentally probed by Ghadimi et al [33]. Sajedi and Ghadimi [28] also experimentally studied the singlestepped hull in the presence of irregular waves.…”
Section: Introductionmentioning
confidence: 99%
“…Tey found that the simultaneous use of stern wedges and transverse steps could improve the vessel's undesirable performance prior to planing regime, which is one of the challenges in planing hull design. Tese extensive data [9,28,29,[31][32][33][34][35][36][37] for diferent confgurations of a single parent model present a unique opportunity to realize how diferent confgurations of step and wedge could afect a planing hull's performance.…”
Section: Introductionmentioning
confidence: 99%